The Correlation between Students' Reading Anxiety and Their Reading Comprehension - Maula Zaki Bunayya; Ag. Bambang Setiyadi; Fajar Riyantika (U-Jet Unila Journal of English Language Teaching, 2026)
The research aims to find out whether or not there was any significant correlation between students’ reading anxiety and their reading comprehension. This study was a quantitative research with sample consisted of 22 students in class VIII.3 of SMP Negeri 1 Pringsewu. The instruments were the Foreign Language Reading Anxiety Scale (FLRAS) questionnaire developed by Saito, Horwitz and Garza (1999) and reading comprehension test. Pearson Product-Moment Correlation was used through SPSS 25 version to analyze the data. The results of this research revealed that there was a significant correlation between students’ reading anxiety and their reading comprehension since r-value -0.678 > r-table 0.423. The data showed that students’ reading anxiety and reading comprehension scores correlates with each other, and the correlation is negative. It means students with higher reading anxiety, associated with lower reading comprehension. And the lower reading anxiety, tend to be followed by the higher reading comprehension.